New record of Epigonus pectinifer Mayer, 1974 (Pempheriformes: Epigonidae) from Tanzania, with the first phylogenetic analysis of the species - Bogorodsky, Sergey V.; Silas, Mathew O.; Reddy, Seshnee (Zootaxa, 2026)
A single specimen of Epigonus pectinifer Mayer, a rare deepwater cardinalfish known from scattered localities in the Atlantic Ocean and Indo-West Pacific, was trawled during a survey conducted by the research vessel Dr. Fridtjof Nansen off Tanzania, representing a new regional record. Epigonus pectinifer belongs to the E. constanciae species group that is characterized by a pungent opercular spine, and it differs from congeners of the group by the following set of characters: a pair of pointed, mustache-like processes on the anterior part of the maxilla; a tongue bearing a tooth patch; a pair of bumps at the symphysis of the lower jaw; and vertebral count of 10 + 15. The specimen is described, illustrated with a photograph taken in fresh condition, and included, for the first time, in a phylogenetic analysis based on the COI barcoding region.